Significance of anti-Ro/SSA antibodies in the response and retention of abatacept in patients with rheumatoid arthritis: a multicentre cohort study. (2nd January 2021) - Endo, Y; Koga, T; Kawashiri, S-y; Morimoto, S; Nishino, A; Okamoto, M; Tsuji, S; Takatani, A; Shimizu, T; Sumiyoshi, R; Igawa, T; Iwamoto, N; et al.
Abstract : Objective : To determine whether the positivity of baseline anti-Ro/Sjögren's syndrome antigen A (SSA) antibodies influences the response to abatacept, we compared therapeutic responses between anti-Ro/SSA antibody-negative and -positive patients with rheumatoid arthritis (RA) using a multicentre RA ultrasonography prospective cohort. Method : We reviewed Japanese patients with RA who started abatacept as the first biological disease-modifying anti-rheumatic drug between June 2013 and April 2018. We assessed 28-joint Disease Activity Score–erythrocyte sedimentation rate (DAS28-ESR) change between baseline and 6 or 12 months after treatment in RA patients treated with abatacept, and European League Against Rheumatism (EULAR) response at 6 and 12 months. The Global OMERACT-EULAR Synovitis Score (GLOESS) was calculated at baseline and at 6 and 12 months. Results : Overall, 51 patients were enrolled and divided into anti-Ro/SSA antibody-negative and -positive groups of 35 and 16, respectively. Median age at baseline was significantly higher in the anti-Ro/SSA antibody-negative group (p = 0.04). The retention rate and percentage of EULAR good responders at 12 months were significantly higher in the anti-Ro/SSA antibody-negative group (both p = 0.02). Anti-Ro/SSA antibody-negative patients exhibited larger decreases in both DAS28-ESR and DAS28-C-reactive protein at 12 months than anti-Ro/SSA antibody-positive patients (p = 0.02 and 0.04, respectively). GLOESS decreased significantly at 6 months in anti-Ro/SSA antibody-negative patients (p = 0.03). Multivariate analyses showed that anti-Ro/SSA antibody positivity was an independent factor associated with change in the DAS28-ESR at 6 months (p < 0.05). Conclusion : Anti-Ro/SSA antibody positivity predicts a poor response to abatacept and low retention rate.